Principles of Tax Collection in Value Added Tax (VAT) on Digital Services in Indonesia - Putri Andreana; Inayati Inayati (Universitas Teuku Umar, 2022)
Indonesia is one of the countries with a high level of consumption of digital services. That potential encourages the government to collect Value Added Tax (VAT) on digital services, including foreign companies. However, in practice, issues related to efficiency and supervision were found. This paper aims to analyze the fulfillment of the principles of tax collection in collecting Value Added Tax (VAT) on digital services. The method used is qualitative with data collection through literature study. The analysis results show that the principle of Equity fulfills horizontal Equity because the fees are charged regardless of ability; Revenue Productivity has succeeded in increasing state revenue; Ease of administration, meets the aspects of certainty, convenience, simplicity, and efficiency. However, in terms of efficiency, it is feared that it could increase compliance costs due to the limited knowledge of PMSE tax. Transparency is not optimal because the absence of a physical presence in Indonesia makes it difficult to access data and information so that supervision is carried out; Neutrality is fulfilled because it supports the competitiveness of local business, while in terms of consumption, it is necessary to pay attention to VAT facilities on digital export services due to the potential for distortion of local digital service providers. So it can be said that the practice of collecting Value Added Tax (VAT) fulfills all aspects. However, several issues need more attention, especially efficiency, transparency, and neutrality.